POTENSI PENGEMBANGAN WISATA HALAL DALAM PERSPEKTIF DUKUNGAN KETERSEDIAAN RESTORAN HALAL LOKAL (NON WARALABA) DI KOTA GORONTALO - Krisna Anugrah (Universitas Merdeka Malang, 2017)
This study focused about the potential development of halal tourism in the perspective support of availability of local halal restaurant (non franchise restaurant) in Gorontalo city. In master plan Gorontalo Tourism Development stated that Gorontalo has potential opportunity to develop halal tourism as one of tourism destination. These potential opportunity supported by few of factor which that the majority of the population are moslem, tourist visitor are dominated by domestic tourist which is connected also to majority of population in Indonesia are moslem as well. The city of Gorontalo as the capital city has many facilities than other city in Gorontalo province. The facilities such as star hotel and non star hotel, franchise restaurant, lokal restaurant. Other than that Gorontalo city has strategic position because situated between two cities that has tourist destination and attraction. This study used descriptive qualitative method. The data obtained through field obeservation, interview, and documentation. All data collected by using sampling purposive technique. the quantitative data obtained will be described in descriptive terms. The completion of this research will presented in descriptive. The results showed the existence of a restaurant that has halal certification is sufficient to support halal tourism. In order to run well required cooperation among stakeholders.